Genetic diversity of East European and Asian strains of tick-borne encephalitis virus belonging to Siberian genotype - L. S. Karan; V. V. Pogodina; T. V. Frolova; A. Ye. Platonov (Бюллетень сибирской медицины)
We have studied 40 strains of tick-borne encephalitis virus attributed to Siberian genotype. The fragment of E gene (211 nt) has been sequenced for all strains. Futher analysis has evidenced the formation of two clusters. One of them includes the strains of East European (EE) origin, the other comprises the strains of Asian origin (A). 17 of 20 East European strains have histidin (H) in amino acid position 234 of gene E, the remaining 3 have either glutamine (Q) or tyrosine (Y). 13 Asian strains have histidine and 7 Asian strains have glutamine in amino acid position 234.